2006
DOI: 10.1021/ja057896y
|View full text |Cite
|
Sign up to set email alerts
|

Dendron-Tethered and Templated CdS Quantum Dots on Single-Walled Carbon Nanotubes

Abstract: CdS nanoparticles on the surface of single-walled carbon nanotubes (SWNTs) were templated and stabilized through the initial attachment of 1 --> 3 C-branched amide-based dendrons and were both photophysically and morphologically characterized. The CdS clusters were shown to be ca. 1.4 nm in diameter as calculated from their optical absorption spectra and exhibited reduced fluorescence emission intensity at 434 nm compared to that of CdS quantum dots stabilized by untethered dendrons due to partial emission que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 52 publications
1
59
0
Order By: Relevance
“…Due to their compact structure and availability of many end groups dendrimers have been used as antimicrobial agents especially quaternary ammonium compounds (QAC) have been widely used as disinfectants [30][31][32]. Dendrimers were used to immobilize metal and semiconductor nanoparticles on the CNTs surface [33][34][35][36][37][38]44]. Imae [34,35] and Zhu and co-workers [39] reported on poly(amidoamine) (PAMAM) dendrimer templates to introduce metal and metal oxide nanoparticles on the surface of MWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their compact structure and availability of many end groups dendrimers have been used as antimicrobial agents especially quaternary ammonium compounds (QAC) have been widely used as disinfectants [30][31][32]. Dendrimers were used to immobilize metal and semiconductor nanoparticles on the CNTs surface [33][34][35][36][37][38]44]. Imae [34,35] and Zhu and co-workers [39] reported on poly(amidoamine) (PAMAM) dendrimer templates to introduce metal and metal oxide nanoparticles on the surface of MWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…1-5) and dendrimers [6][7][8][9] are broad range chemical platforms, being actively pursued in recent years for physicochemical, [10][11][12][13] biological, [14][15][16][17][18][19][20][21][22][23] and materials related studies. [24][25][26][27][28][29][30][31][32] In biological applications, SWNTs have been demonstrated as synthetic vectors for efficient delivery of nucleic acids, proteins, and sugars. [14][15][16][17][18][19][20][21][22][23] It has been shown that membranes which are impermeable otherwise become permeable to ligands mediated by SWNTs.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of stable CdS nanoparticles on the oxygentated surface of SWNTs templated and stabilized by means of attached 1 → 3 C-branched amide-based dendrons was also reported (21).…”
Section: Ends and Defect Sitesmentioning
confidence: 93%